Cerebellar brain inhibition in the target and surround muscles during voluntary tonic activation. (28th March 2016) - Panyakaew, Pattamon; Cho, Hyun Joo; Srivanitchapoom, Prachaya; Popa, Traian; Wu, Tianxia; Hallett, Mark
Abstract: Motor surround inhibition is the neural mechanism that selectively favours the contraction of target muscles and inhibits nearby muscles to prevent unwanted movements. This inhibition was previously reported at the onset of a movement, but not during a tonic contraction. Cerebellar brain inhibition (CBI) is reduced in active muscles during tonic activation; however, it has not been studied in the surround muscles. CBI was evaluated in the first dorsal interosseus (FDI) muscle as the target muscle, and the abductor digiti minimi, flexor carpi radialis and extensor carpi radialis muscles as surround muscles, during rest and tonic activation of the FDI muscle in 21 subjects. Cerebellar stimulation was performed under magnetic resonance imaging‐guided neuronavigation targeting lobule VIII of the cerebellar hemisphere. Stimulus intensities for cerebellar stimulation were based on the resting motor cortex threshold (RMT) and adjusted for the depth difference between the cerebellar and motor cortices. We used 90–120% of the adjusted RMT as the conditioning stimulus intensity during rest. The intensity that generated the best CBI at rest in the FDI muscle was selected for use during tonic activation. During selective tonic activation of the FDI muscle, CBI was significantly reduced only for the FDI muscle, and not for the surround muscles. Unconditioned motor evoked potential sizes were increased in all muscles during FDI muscle tonic activation as compared with rest, despite background electromyography activity increasing only for the FDI muscle. Our study suggests that the cerebellum may play an important role in selective tonic finger movement by reducing its inhibition in the motor cortex only for the relevant agonist muscle. Abstract : Cerebellar brain inhibition (CBI) decreases in the target muscle and not in the surround muscles during the tonic phase of movement, possibly contributing to sharpening of the motor command.